Multilevel habitat preferences of Apodemus sylvaticus and Clethrionomys glareolus in an intensively cultivated agricultural landscape. Issue 1 (2nd January 2017) - Balestrieri, A.; Remonti, L.; Morotti, L.; Saino, N.; Prigioni, C.; Guidali, F.
Abstract : Small mammals are considered good model species for assessing the global effects of habitat loss and fragmentation in agricultural landscapes. With the aim of investigating the composition and habitat preferences of the small mammal community in an intensively cultivated area, we sampled the three main "macro-habitats" (wood patches, poplar plantations and crops) available on the western plain of the River Po (North Italy). The influence of habitat variables on each species' occurrence was assessed at three different scales of observation: "macro-habitat", "micro-habitat" (i.e. vegetation layers at trap sites) and the landscape level (i.e. land cover in plots of 500 m radius centred on each trap line). Overall, 3344 trap-nights yielded 169 Apodemus sylvaticus, 28 Clethrionomys glareolus and two Sorex araneus . The first species was dominant in all macro-habitats, while the other two species were trapped only in residual wood patches. The thickness of the fine litter was the main micro-habitat factor affecting the occurrence of both C. glareolus and A. sylvaticus in woods, while sites with herbaceous vegetation cover were preferred by the latter species in poplar plantations. Intraclass correlation coefficients showed that sites with thick litter or high herb cover were neither exclusive nor predominant in wood patches and poplar plantations, respectively, suggesting that the choice for micro-habitat parameters is subordinate to that of macro-habitat characteristics, mainly tree and shrub cover. At the landscape scale, no habitat variable affected the occurrence of both species. At the macro-habitat level, the strong selection for wood patches by both wood mice and bank voles and the negligible occurrence of small mammals in cultivated plots pointed out the major role for conservation played by residual semi-natural habitats in agricultural landscapes.